Terapi Latihan Fisik Pada Pasien Cedera Meniskus Tanpa Tindakan Operatif: Laporan Kasus Berbasis Bukti - Diczen Diczen; Nani Cahyani Sudarsono (Majalah Kedokteran Indonesia, 2024)
Introduction: Surgery for meniscus injuries has the potential to trigger osteoarthritis and early cartilage degeneration. This evidence-based case report aims to evaluate the effectiveness of physical exercise therapy compared to surgery in restoring knee function in a woman with a lateral discoid meniscus tear.Methods: A systematic literature search was conducted using databases such as PubMed, ScienceDirect, ProQuest, and Scopus. The focus of the search was on studies comparing the outcomes of physical exercise therapy and surgery for meniscus injuries.Result: Out of 737 identified articles, three relevant studies met the criteria and addressed the research question of this case report. These studies concluded that there was no significant difference between physical exercise therapy and surgery in restoring knee function in patients with meniscus injuries.Conclusion: Physical exercise therapy has proven effective as a safe alternative with the potential to reduce the risk of operative complications in patients with meniscus injuries. This non-invasive approach offers a viable option for maintaining knee function without increasing the risk of osteoarthritis or early cartilage degeneration.